Role of Forensic Investigations in Reduction of Financial Fraud Among Commercial Banks in South Sudan - Mabior, Maliap Madit; Wanyama, Kadian Wanyonyi (East African Nature and Science Organization, 2024)
Financial fraud poses a significant challenge to the banking sector globally, including South Sudan. This study aimed to investigate the effectiveness of forensic investigations in mitigating financial fraud within commercial banks. Employing a mixed-methods approach and an explanatory research design, the study targeted 119 respondents and nine commercial banks. Data was analysed using descriptive statistics and regression analyses. The findings revealed a strong association between increased levels of forensic investigations and a significant reduction in financial fraud among commercial banks in South Sudan. The study emphasized the crucial role of adopting sophisticated technologies like data analytics and forensic accounting techniques, as well as implementing robust internal control mechanisms, in enhancing the effectiveness of forensic investigations. Through bolstering forensic investigation practices, not only can financial fraud be curbed, but the overall integrity and trustworthiness of South Sudan's banking sector can be enhanced. To address financial fraud effectively, the study recommended that commercial banks invest in advanced forensic investigation tools and technologies, enabling them to better detect and prevent fraudulent activities. Furthermore, enhancing the training and capacity-building of forensic professionals within these institutions was identified as a means to improve their effectiveness in dealing with fraud. Strengthening internal control systems and fostering a culture of transparency and accountability were also highlighted as vital steps. This research holds significance in informing policy and practice within South Sudan's banking sector. Through highlighting the effectiveness of forensic investigations in combating financial fraud, the study emphasizes the importance of prioritizing forensic capabilities within commercial banks. Moreover, it contributes to the existing literature on forensic investigations and financial fraud, offering valuable insights for researchers and policymakers alike